Development of Tilapia (Oreochromis niloticus) cultivation in Talaga Paca North Halmahera Regency - Eteke, Charlly Natalia (Agrikan: Jurnal Agribisnis Perikanan, 2021)
Lake Talaga Paca is one of the lakes in North Halmahera regency used for various purpouse by the community around. The utilizing of lake water for household purposes, transportation and fish cultivation with KJA or KJT. This study aim to determine the strategy of development of the tilapia (Oreochromis niloticus) in Talaga Paca. The method used in this research was descriptive research with data collection techniques used interviews and observations. To formulate a development strategy, based on the results of internal and external factor identification which is then tabulated in the form of IFAS matrix and EFAS matrix, next use the SWOT matrix. The result of water quality measurements are still in a good range. The result of the SWOT analysis results in four strategies that can be used for the development of tilapia fish (Oreochromis niloticus) ie land optimization cultivation area in Talaga Paca becomes more productive and sustainable, improving the ability of cultivators through training and coaching related to the good aquaculture practice and training of fish feed making to tackle the high problem of fish feed prices, agreement between the Cultivators and the community to maintain security at cultivation site.